(3EVGAI GdQGehS MGTjI Ydi GdbGehSs - (3eMeO Hf GdWjH eMeO Hf eMeO Hf eMeO GdTQbj GdaGSj GdeGdcj, CHh YHO Gddg , J (B1170 (3g`s; (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3HGH GdMGA GdegedI aUd GdgeRI bhdg GdGLGM s
(3BNQgG (B:s
(3Cf GHQGgje GdNdjd Ydjg GdSdGe hGddg SHMGfg hJYGdi GYde GfJgi GdLRA GdKGdK s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRjOGfjI ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(3 / 544) s
Keywords: (3GddZIs